2010
DOI: 10.1136/gut.2009.197822
|View full text |Cite
|
Sign up to set email alerts
|

Colitis induced in mice with dextran sulfate sodium (DSS) is mediated by the NLRP3 inflammasome

Abstract: BackgroundThe proinflammatory cytokines interleukin 1b (IL-1b) and IL-18 are central players in the pathogenesis of inflammatory bowel disease (IBD). In response to a variety of microbial components and crystalline substances, both cytokines are processed via the caspase-1-activating multiprotein complex, the NLRP3 inflammasome. Here, the role of the NLRP3 inflammasome in experimental colitis induced by dextran sodium sulfate (DSS) was examined. Methods IL-1b production in response to DSS was studied in macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
482
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 762 publications
(507 citation statements)
references
References 39 publications
(47 reference statements)
18
482
5
2
Order By: Relevance
“…Combined, these data suggest that in mice lacking the pan-inflammasome adaptor protein ASC, there is an outgrowth of bacteria that could be implicated in a dysbiotic microbiome. This interpretation would be consistent with the previously reported increased sensitivity of these mice to models of experimental colitis and colitis-associated cancer [18, 29]. …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Combined, these data suggest that in mice lacking the pan-inflammasome adaptor protein ASC, there is an outgrowth of bacteria that could be implicated in a dysbiotic microbiome. This interpretation would be consistent with the previously reported increased sensitivity of these mice to models of experimental colitis and colitis-associated cancer [18, 29]. …”
Section: Resultssupporting
confidence: 82%
“…Mice lacking the pan-inflammasome adaptor protein ASC are highly sensitive to experimental colitis and demonstrate significantly increased inflammation-driven colon tumorigenesis [9-11, 15, 29]. Surprisingly, there are few comprehensive studies evaluating the microbiome composition in the Asc –/– mice under naïve conditions and, of those that have been conducted, there is currently conflicting data regarding the role of ASC in shaping the commensal gut microbiota composition [18, 21].…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of data from gene-deleted mouse models showed that the NLRP3 inflammasome protects against experimental colitis 36 and colitis-associated tumorigenesis, 37 whereas other groups demonstrated that NLRP3-PYCARD-CASP1-mediated maturation of IL1B is essential for DSS-induced experimental colitis and nlrp3 −/− mice develop a less severe colitis than wildtype mice. [38][39][40][41] Bauer et al pointed out that these contradictions might result from the different composition of the intestinal microflora. 41 Unlike the controversies resulting from genedeleted mouse models, IL18 neutralization, 42,43 or chemical CASP1 inhibitor 44,45 treatment effectively reduce severity in murine colitis.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, various derivatives of dextran have shown to have immunological properties. The sulphatederivatized form of dextran sulphate was shown to have anti-inflammatory properties in vivo and it was used in the induction of inflammatory colitis in mice [13]. Another derivative, diethylaminoethyl dextran (DEAED), is polycationic in nature and has been used as a vaccine adjuvant.…”
Section: Natural Polymersmentioning
confidence: 99%